2021
DOI: 10.1002/cncy.22432
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of risk of malignancy by application of the proposed Sydney system for classification and reporting lymph node cytopathology

Abstract: BACKGROUND Fine‐needle aspiration cytology (FNAC) is one of the most commonly used techniques for evaluating lymphadenopathy. Recently, the Sydney system was proposed for assessing the performance, classification, and reporting of lymph node (LN) cytopathology. The present study was conducted to assess the risk of malignancy associated with each of the diagnostic categories of the proposed Sydney system. METHODS This was a 2‐year retrospective study of LN‐FNAs; cytologic diagnoses were categorized by the propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

39
60
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(133 citation statements)
references
References 31 publications
39
60
7
Order By: Relevance
“…Our series showed very high specificity and PPV, in accordance with previous studies 4,5,9,11,12 . We had only one FP case, consisting of a lymph node suspicious for papillary thyroid carcinoma metastasis.…”
Section: Discussionsupporting
confidence: 91%
“…Our series showed very high specificity and PPV, in accordance with previous studies 4,5,9,11,12 . We had only one FP case, consisting of a lymph node suspicious for papillary thyroid carcinoma metastasis.…”
Section: Discussionsupporting
confidence: 91%
“…From our experience, we believe that this low-rate of insufficient samples is due to several factors: the superficial location of the lymphadenopathies (which makes them relatively easier to access), the expertise of the interventional pathologist performing USFNA, and the real-time decision-making associated with ROSE and sample management. As expected, more than half of the lymphadenopathies corresponded to the benign category, in line with other studies [11,35]. All cases of atypia of uncertain significance were classified in the subcategory atypical lymphoid cells of uncertain significance, similar to the majority of cases in the suspicious category, in which 19 of 21 specimens were suggestive of a lymphoproliferative process.…”
Section: Discussionsupporting
confidence: 90%
“…Reclassifying our system into the Sydney system categories revealed that the rate of samples with inadequate/ insufficient results was <4%, 1 of the lowest reported to date [3,34]. This is in agreement with 1 of the few articles published that addresses the applicability of the Sydney system [35]. From our experience, we believe that this low-rate of insufficient samples is due to several factors: the superficial location of the lymphadenopathies (which makes them relatively easier to access), the expertise of the interventional pathologist performing USFNA, and the real-time decision-making associated with ROSE and sample management.…”
Section: Discussionsupporting
confidence: 86%
“…As expected, the L2 category showed the lowest ROM (1.92%). Notably, in our series, few infective lymphadenopaties were present; however, the utility of FNC as a noninvasive procedure in this setting in most parts of the world cannot be overemphasized [26]. Interestingly, the two FN diagnoses were represented by subcapsular breast metastases in axillary lymph nodes, highlighting that partial lymph nodal involvement must be considered as a possible cause of misclassification (Figure 1).…”
Section: Discussionmentioning
confidence: 74%
“…To fulfil the latter requirement, in 2020, an expert panel published the proposal of the Sydney system for performing classification and reporting of lymph node cytopathology, introducing the use of five diagnostic categories [25]; moreover, taking into account the wide spectrum of lymph node pathologies, a second diagnostic level, aimed at the identification of specific diagnostic entities, has been proposed. However, the Sydney system is still underutilized and to date there are limited data in the literature [26]. To fill this knowledge gap, the aim of the present study was to evaluate the applicability of the Sydney system to lymph node FNC and to assess the diagnostic accuracy and the risk of malignancy (ROM) for each diagnostic category.…”
Section: Introductionmentioning
confidence: 99%